A mathematical model for managing XML data. (1st January 2011) - Serna Nocedal, Ainhoa; Gerrikagoitia Arrien, Jon Kepa; Burgin, Mark
This paper presents a new algebra for data preparation, processing, search and acquisition. This data management algebra is called CNS-algebra. The proposed data meta-model provides an efficient mathematical model for data gathering on the web. This unified data meta-model is suitable for data models on all levels: from high- or conceptual-level to low- or physical-level models. In the paper, we show how this model can be applied to processing XML documents and schemas.